Impact of multidisciplinary patient education sessions on expectations and understanding of new calcitonin gene-related peptide treatments. (3rd September 2019) - Stewart, Alyssa; Wells, Rebecca; Young, Jennifer; Strauss, Lauren; Wise, Starla; Granetzke, Laura; Kumar, Sandhya; Speiser, Jaime; Guzik, Amy; O'Connell, Nathaniel
Abstract: Background: The new calcitonin gene-related peptide (CGRP) medications offer an exciting alternative to daily preventative migraine treatments. Finding effective and efficient ways to educate patients can be challenging for providers and pharmacists alike given the treatments are subcutaneous injections with extended half-lives and data is limited on long-term efficacy and adverse effects. Aims: We aimed to develop and evaluate a patient-oriented, multidisciplinary presentation to inform patients about the new CGRP drug class to decrease provider and pharmacist education burden while increasing patient understanding. Methods: Three live, one-hour CGRP informational sessions were conducted jointly by a headache medicine neurologist and clinical pharmacist from the institution's specialty pharmacy. Prior to medication initiation, patients were educated about CGRP pathophysiology, benefits, risks, injection technique, and logistics of cost and medication access. The third presentation was video recorded and transitioned to an online platform. Participants completed surveys before and after watching the in-person or online session. Patients had the ability to fill these self-injectable therapies at the institution's specialty pharmacy, who assisted with benefits investigation and prior authorization. If within payor network, the patient was offered specialty pharmacy services. Results: A total of 84 patients participated in the session (41 in-person; 43 online). Patients had frequent headaches (mean = 18/month; SD = 9.2) with severe (MIDAS >21) headache-related disability (mean MIDAS score = 63.1). Participants reporting confidence in understanding CGRP significantly increased from 68% to 97% following the informational session ( p  < .001) for those completing both the pre- and post-survey question ( n  = 69). There was also a significant increase from 84% to 97% in participants reporting comfort with injection technique ( p  = .008, n  = 70). For both measures, there was no statistically significant difference between the in-person and online sessions. Nearly all participants (97%) would recommend the session to family or friends with migraine. Conclusions: The multidisciplinary informational session was an effective and efficient method of educating patients about these new treatments while concurrently decreasing provider and pharmacist education burden. The online video was as effective as the in-person session in educating patients, but improved access and availability.